Hunting practices in northern Australia and their implication for disease transmission between community dogs and wild dogs. Issue 8 (17th June 2019) - Gabriele‐Rivet, V; Brookes, VJ; Arsenault, J; Ward, MP
Abstract : Objective: This survey aimed to understand hunting practices involving domestic dogs in remote Indigenous communities in northern Australia and, in the context of disease transmission, describe the domestic–wild dog interface and intercommunity interactions of hunting dogs during hunting activities. Methods: A cross‐sectional survey of 13 hunters from communities of the Northern Peninsula Area (NPA) of Queensland gathered information on demographics of hunters and hunting dogs, hunting practices and past encounters with wild dogs during hunting trips. Social networks that described the connections of hunters between NPA communities from hunting expeditions were developed. Results: Most hunters interviewed were not aware of any diseases that could be transmitted to dogs (n = 11) or humans (n = 9) from wild animals while hunting. More than half (n = 7) of the respondents had experienced at least one wild dog encounter during hunting in the year prior to the interview. A map of the relative risk of interactions between wild and hunting dogs during hunting trips allowed the identification of high‐risk areas in the NPA; these areas are characterised by dense rainforests. The social networks at the community level resulted in relatively large density measures reflecting a high level of intercommunity connectedness. Conclusions: This study contributes to our knowledge of Australian Indigenous hunting practices and supports the potential for disease transmission at the domestic–wild dog interface and intercommunity level through contacts between hunting dogs during hunting activities. Insights from this study also highlight the need for educational programs on disease management in Indigenous communities of northern Australia.